(untitled) (Scientific journal of the Fergana State University, 2024)
The relevance of the problem of development of speech competence of elementary school students confirms the need for a deep understanding of the pedagogical and psychological characteristics that affect this process. This article provides a theoretical overview of research on language acquisition in elementary school children, highlighting key aspects that influence effective instructional design. The purpose of designing the process of development of speech competence of elementary school students: to create a holistic and effective educational environment that helps to develop speech competence of elementary school students. This includes the formation of fluent and competent communication skills, as well as the development of vocabulary, the ability to analyze and understand text, and adequately express one’s thoughts.